Penerapan Tehnik Pengolahan Limbah Rumah Tangga Dengan Cacing Tanah Pada Kelompok Tani Kampung Bunga Raya Siak - Yusfiati, Yusfiati; Chahyadi, Eni; Iriani, Dyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The application how processing to fertilizer from household waste with earthworms aims to add positive and productive activities among the farmers of Kampung Bunga Raya in order to increase the economic value of farmers' income.The method used was counseling and direct practice in the field with 19 participants from farmer groups. The results obtained are 1 kg of household waste can produce 2 kg of organic fertilizer and 500 grams of worms. The fertilizer obtained can be used for oil palm plantations and gardening of farming communities in Bunga Raya village, Bunga Raya district, Siak. The Cultivation of earthworms are using household waste can overcome the problem of availability of fertilizer for plantations.